Study on The Disaster Manageement In Indonesia - Andi Dibya Widadi (Lowland Technology International, 2020)
Palu City is one of the provincial capitals in Indonesia which is right on the Equator line. In addition, this city is one of the many regions in the eastern part of Indonesia that have a considerable potential for natural disasters. The natural disaster that occurred in Palu on September 28, 2018 consisted of three types of disasters, the first was an earthquake, the second tsunami and the last was liquefaction. This natural disaster caused damage to supporting infrastructure and thousands of people died. The large number of fatalities illustrates that the preparation and preparedness of the community and local government authorities are still low, mainly due to a lack of knowledge and concern for these natural phenomena and their consequences. The earthquake and tsunami disaster that took place in the city of Palu Sigi and Donggala was a momentum to change the paradigm of disaster management by increasing community preparedness. This research tells the story of the phenomenon of the three natural disasters, also tried to explain the steps and design of disaster mitigation. Disaster Mitigation must be implemented to reduce the risk of natural disasters. Public policy about community preparedness towards disaster management is very important and urgent to do in order to reduce disaster risk. Disaster cases in Palu City as a case study are considered relevant for the implementation of disaster management systems.